KAJIAN KOMPARATIF AL-QUR’AN DAN WEDA TENTANG MODERASI BERAGAMA - Pramana, M. Syarif Adi; Noor, Muhammad Fauzi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat of Institut Agama Islam Negeri Metro, 2024)
Indonesia is famous for its diverse tribes, languages, and beliefs, a fact that can not be disputed by the people of Indonesia. They will not separate the diversity in Indonesia from the conflicts that arise in people's lives caused by various factors. Then religious moderation is one of the efforts or middle ground that occurs in the lives of Indonesian people to maintain the integrity and harmony that has long been built. In addition, it also prevents extreme and radical thoughts and exaggerated attitudes that arise in social life, both in the social and spiritual spheres. This article uses a qualitative method, library research with an analysis comparing the text of the Qur'an with the Vedas, which discusses religious moderation. The results in this paper state that the teachings of Islam and Hinduism, when talking about religious moderation, it turns out that many have in common, which ultimately leads to several important points: no one religious teaching wants division in it, does not force to embrace the same teachings, build peace and happiness in life, even united in living life in the world as a whole society because everything is one family that has the same purpose in life in the world.